Cloud Computing: Going Global - Jainab Zareena, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Cloud computing is the concept that emerged recently. After its introduction, there is a massive change in industries. Specifically, industries holding IT resources welcome cloud computing services. Presently, the term â€˜Public Cloudâ€™ is also introduced in educational sector. Earlier research studies considered cloud computing as a beneficial factor. Cloud computing services are used globally and organizations have obtained more profit out of it. One such good example is Microsoft Azure. This paper briefly reviews those studies underlying the concept â€˜cloud computingâ€™. It enables the readers to understand the utility of cloud computing in enterprises.Â Â